Maladaptive perfectionism can explain the inverse relationship between dispositional mindfulness and procrastination - Gozde Ibili; Jeremy John Tree; Yılmaz Orhun Gurluk (PLoS ONE, 2025)
Given the widespread occurrence of procrastination and its adverse association with well-being, investigating the individual variables that influence procrastination is a crucial matter. Previous research has identified dispositional mindfulness to be negatively associated with procrastination, but the underlying mechanisms driving this relationship remain unclear. In this study, the aim was to investigate whether the inverse relationship between dispositional mindfulness and procrastination could be explained by the mediating roles of trait anxiety and maladaptive perfectionism. In a cross-sectional survey, 126 participants (aged 18–33) completed the 15-Item Five-Facet Mindfulness Questionnaire, the State-Trait Anxiety Inventory-Trait Form, the Almost Perfect Scale-Revised, and the Pure Procrastination Scale. A parallel mediation model was tested to investigate the mediating role of self-reported maladaptive perfectionism and trait anxiety to explain the relationship between dispositional mindfulness and procrastination with a bootstrapped multivariate technique. The results revealed that maladaptive perfectionism significantly mediated the relationship between mindfulness and procrastination -indicating that dispositional mindfulness has a significant indirect effect on procrastination via decreased levels of maladaptive perfectionism. It was determined that 15% of the variance in procrastination was significantly explained by this model (R2 = .15, β =  −.39, B =  −.83, 95% CI =  [−1.18, −.48], p < .001]. As the study highlights the importance of maladaptive perfectionism to explain the link between mindfulness and procrastination, we suggest that future research could investigate the influence of mindfulness on procrastination via mindfulness-based interventions, and include measurements of both trait anxiety and maladaptive perfectionism across longitudinal or experimental designs to unpack causality with respect to our pattern of observed findings.